Carbon Footprint Optimization in Nickel-Based Industrial Development: A Case Study of IMIP Morowali Through Sustainable Supply Chain Management Approach - Oetomo, Dedy Setyo; Hermawan, Asep; Iskandar, Hendi (Yayasan Gema Bina Nusantara, 2025)
This research investigates carbon footprint optimisation strategies in the nickel-based industrial development at Indonesia Morowali Industrial Park (IMIP), focusing on sustainable supply chain management practices. The study employs a mixed-method approach, combining quantitative analysis of carbon emissions data with qualitative assessment of supply chain processes. Through comprehensive data collection from 2019-2024 and analysis of multiple operational parameters, the research identified key optimisation opportunities across mining operations, processing plants, and transportation networks. Results indicate that implementing targeted optimisation strategies across the supply chain could reduce carbon emissions by 15-20% while maintaining production efficiency. Specific interventions, including waste heat recovery systems, fleet electrification, and smart logistics integration, demonstrated significant impact with potential annual savings of 87,500 tCO2e and 11.2 million in operational costs. The study also revealed that integrating sustainable practices led to an 18% improvement in production efficiency and a 12% enhancement in resource recovery rates. The findings contribute to the growing knowledge of sustainable industrial development in the mining and metallurgical sectors, offering practical insights for similar industrial parks globally. This research provides valuable frameworks for balancing environmental sustainability with industrial growth in emerging economies.